Characteristics of Cancer Patients Enrolled for Radiotherapy in Andalas University Hospital - Hanggara, Muhammad Azzel; Hanum, Fathiya Juwita; Adrial (Frontiers on Healthcare Research, 2025)
Background: Cancer remains a significant global health burden, with radiotherapy being a crucial treatment modality. However, data on the characteristics of cancer patients undergoing radiotherapy in West Sumatra is limited. This study aims to analyze the demographic and clinical characteristics of patients receiving radiotherapy at Andalas University Hospital. Methods: A retrospective descriptive study was conducted on 510 cancer patients who underwent radiotherapy between 2019 and 2020. Data were collected from medical records, including demographics, cancer types, staging, and treatment history. Results: Breast cancer (42.5%) was the most common malignancy, with a higher prevalence in female patients (72.5%), particularly in the 45–64 age group. Stage IV (26.1%) was the most frequently recorded staging, though nearly 50% of cases lacked staging data, highlighting documentation gaps. The majority of patients were from West Sumatra (78.6%), with a significant number referred from other provinces, emphasizing Andalas University Hospital’s role as a regional referral center for radiotherapy. Conclusion: The findings underscore the high prevalence of late-stage cancer diagnoses and incomplete medical records, necessitating enhanced cancer registration systems and early detection programs. Strengthening data management and accessibility is crucial for improving cancer care and treatment outcomes in West Sumatra.